2023
DOI: 10.2174/1567202620666230727153306
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Studies of REST Gene Associated Neurological Diseases/traits with Related Single Nucleotide Polymorphisms

Abstract: Background: Genome-wide association studies (GWAS) have been used to explore the connections between genotypes and phenotypes by comparing the genotype frequencies of genetic changes in individuals with similar origins but distinct traits. Objectives: The aim is to employ the GWAS catalog to identify and investigate the various correlations between genotypes and phenotypes of the REST gene. Method: In this study, we utilized a large dataset of GWAS comprising 62,218,976 individuals in 112 studies and 122 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Recently, a GWAS implicated REST and its extended gene network with cognitive decline (Wang et al, 2023), indicating that perhaps genetic variations of REST could account for the betweenindividual variability in the brain aging phenotype. An obvious area of mechanistic exploration would be how REST influences biological aging hallmarks such as cellular senescence.…”
Section: Repressor Element-1-silencing Transcription Factormentioning
confidence: 99%
“…Recently, a GWAS implicated REST and its extended gene network with cognitive decline (Wang et al, 2023), indicating that perhaps genetic variations of REST could account for the betweenindividual variability in the brain aging phenotype. An obvious area of mechanistic exploration would be how REST influences biological aging hallmarks such as cellular senescence.…”
Section: Repressor Element-1-silencing Transcription Factormentioning
confidence: 99%
“…Genomic studies play a pivotal role in identifying genetic variations associated with diseases. Notably, genome-wide association studies have unveiled single nucleotide polymorphisms (SNPs) associated with specific diseases ( Wang et al, 2023 ). In this Research Topic, Liu et al found that miR-196a2 rs11614913 and miR-27a rs895819 may influence genetic susceptibility to gastric precancerous lesions (GPL) or gastric cancer (GC).…”
mentioning
confidence: 99%